Internalisasi Kearifan Lokal Huma Betang Sebagai Upaya Pencegahan Paham Radikalisme - Solikin, Asep (Pedagogik: Jurnal Pendidikan, 2024)
In the last few weeks there has been a quite striking sight with the proliferation of large banners and billboards which speak of calls for massive efforts to resist and combat intolerance, radicalism and terrorism. It is admitted that radicalism, which is currently a trend and in the news recently, is not only a problem experienced by the government. This global ideology has become a common enemy for Indonesian people from all walks of life who may be exposed to these dangers. Much has been done in the form of programs and prevention efforts carried out by the government in order to tackle radicalism, carried out through a method known as deradicalization, not only the government's responsibility, but also the activeness of universities in preventing ideology, spreading antidotes and socializing countermeasures. Deradicalization is an effort to reduce radical activities and neutralize radical ideas for those involved and indicated to follow these methods. There are actually many ways to reduce, control and prevent the massive radicalism that is currently so massive. One of them is an effort to internalize the local wisdom of Huma Betang as one of many approaches. at University. In the researcher's view, this is a good step as a process of incorporating and anchoring the code of conduct and life guidelines of the Dayak people of Central Kalimantan which have been tested for a long time in the form of noble Belom Bahadat (civilized and ethical living), handep is (mutual help), Hampahari /Pahari (brotherhood and togetherness in life) and Hapakat Basara (mutual consensus in life).